Harnessing Knowledge on Very Important Pharmacogenes CYP2C9 and CYP2C19 Variation for Precision Medicine in Resource-Limited Global Conflict Zones - (:unkn) unknown (MARY ANN LIEBERT, INC, 2016)
Pharmacogenomics harnesses the utility of a patient's genome (n=1) in decisions on which therapeutic drugs and in what amounts should be administered. Often, patients with shared ancestry present with comparable genetic profiles that predict drug response. However, populations are not static, thus, often, population mobility through migration, especially enmasse as is seen for refugees, changes the pharmacogenetic profiles of resultant populations and therefore observed responses to commonly used therapeutic drugs. For example, in the aftermath of the Syrian civil war since 2011, millions have fled their homes to neighboring countries in the Middle East. The growing permanence of refugees and mass migrations is a call to shift our focus in the life sciences community from old models of pharmaceutical innovation. These seismic social changes demand faster decisions for population-to-population bridging, whereby novel drugs developed in or for particular regions/countries can meet with rational regulatory decisions/approval in world regions impacted by migrant/refugee populations whose profiles are dynamic, such as in the Eastern Mediterranean region at present. Thus, it is important to characterize and report on the prevalence of pharmacogenes that affect commonly used medications and predict if population changes may call for attention to particular differences that may impact health of patients. Thus, we report here on four single-nucleotide polymorphism (SNP) variations in CYP2C9 and CYP2C19 genes among Mersin-Turkish healthy volunteers in the Mersin Province in the Eastern Mediterranean region that is currently hosting a vast number of migrant populations from Syria. Both CYP2C9 and CYP2C19 are very important pharmacogene molecular targets. We compare and report here on the observed SNP genetic variation in our sample with data on 12 world populations from dbSNP and discuss the feasibility of forecasting the pharmacokinetics of drugs utilized by migrant communities in Mersin and the Eastern Mediterranean region. This study can serve as a catalyst to invest in research in Syrian populations currently living in the Eastern Mediterranean. The findings have salience for rapid and rational regulatory decision-making for worldwide precision medicine and, specifically, pharmacogenovigilance-guided bridging of pharmacokinetics across world populations in the current era of planetary scale migration.
Keywords: GENETIC POLYMORPHISMS; GENOTYPE FREQUENCIES; POPULATION; ALLELE